1996
DOI: 10.1002/(sici)1097-461x(1996)58:1<11::aid-qua2>3.0.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

Monotonicity properties of the atomic charge density function

Abstract: rnThe present knowledge of the monotonicity properties of the spherically averaged electron density p ( r ) and its derivatives, which comes mostly from Roothan-Hartree-Fock calculations, is reviewed and extended to all Hartree-Fock ground-state atoms from hydrogen ( Z = 1) to uranium ( Z = 92). In looking for electron functions with universal (i.e., valid in the whole periodic table) monotonicity properties, it is found that there exist positive values of ct so that the function g o ( r ; ct) = p( r ) / r a i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…The benefits of working with V ( r ) have been demonstrated. For example: Although it is known empirically that ρ ( r ) decreases monotonically with radial distance from the nucleus of a ground‐state neutral atom,11,62 proving this remains a challenge. But demonstrating that V ( r ) must behave in this manner is straightforward, using Poisson's equation 11,12…”
Section: The Diverse Aspects Of the Electrostatic Potentialmentioning
confidence: 99%
“…The benefits of working with V ( r ) have been demonstrated. For example: Although it is known empirically that ρ ( r ) decreases monotonically with radial distance from the nucleus of a ground‐state neutral atom,11,62 proving this remains a challenge. But demonstrating that V ( r ) must behave in this manner is straightforward, using Poisson's equation 11,12…”
Section: The Diverse Aspects Of the Electrostatic Potentialmentioning
confidence: 99%
“…In ref 19 this is shown to be true for the electron density outside a sphere with a certain radius r and for r f ∞. For the region close to the core the Kato cusp condition states that the density is monotonic in this region, and although there is still no formal proof, 8 there exists further computational evidence that the atomic density is indeed a monotonically decaying function for all values of r. [1][2][3][4][5][6][7]9 Therefore, many functions derived from the total electron density have been proposed as a tool to recover the shell structure and to visualize the Aufbau principle. The first studies focused on the radial density distribution function D(r) which was shown to exhibit maxima that correspond to the electronic shells of atoms.…”
Section: Introductionmentioning
confidence: 99%
“…To answer this question, it seems legitimate to consider the one‐electron density of free atoms at first step. It is well‐known computationally that the ground state normalρatomtrue(truertrue) of a free atom reveals a single attractor, a (3, −3) critical point, at the position of nucleus while normalρatomtrue(truertrue) decays “monotonically” far from the nucleus (check Figure ), however, from theoretical viewpoint, this is not a proven conjecture yet . On the other hand, if the free atom's one‐electron density is perturbed marginally in a molecule because of interaction with other AIM, it seems reasonable to assume that the one‐electron density of a molecule is nearly the sum of the one‐electron densities of the constituent free atoms, normalρmoltrue(truertrue)inormalρatom,itrue(truertrue), which is officially called the promolecule model of the one‐electron density (for examples as well as a recent bibliography on this model see ).…”
Section: Open Problems and Corresponding Backgroundmentioning
confidence: 99%